Inquiry, critique, and the intelligible : an interpretation of Horkheimer’s Liturgical Turn - Burns, Robert W. (The University of Edinburgh, 2012)
Max Horkheimer’s mature works on theology and Schopenhauerian metaphysics have been portrayed by subsequent critical theorists as an illicit regression from his earlier social theory in a two-fold sense. First, his concern to reflect on empirical experience is replaced with speculation regarding intelligible concepts, i.e. concepts that do not arise from observation on the basis of sense-intuition but are rather products of “pure” reason (God) or the imagination (Schopenhauer’s will). Second, his advocacy of the Enlightenment as an emancipatory political project is replaced by its skeptical critique. I argue that this consensus radically misunderstands the concerns animating the late Horkheimer insofar as his reflections on intelligible concepts are both intimately related to a continuing concern with empirical inquiry, as well as an outworking of his commitment to the realization of the Enlightenment. The argument is presented in three related movements. In the first, I interpret Horkheimer’s oeuvre in terms of his pervasive interest in developing a materialist logic. I begin by outlining his early understanding of thought as a form of inquiry for embodied social subjects (chapter 1), before noting how, in his mature theorizing, this account serves as a basis for a presentation of the relationship between various kinds of inquiry and the practice of social critique (chapter 2). In the second, I contend that Horkheimer’s critique of instrumental reason is best understood as congruent with this materialist logic, not as a speculative departure from an earlier concern with empirical inquiry. I begin by examining Horkheimer’s empirical analysis of how historical changes in the basic institutions defining political economy in modern life affect the reasoning habits of subjects (chapter 3). I then turn to his diagnosis of the way such changes affect the selfunderstanding of modern subjects, leading to a pervasive form of alienation (chapter 4). In the final movement, I present Horkheimer’s turn to theological concepts of the intelligible as a therapeutic response to this alienation. First, I examine his understanding of the content of theological concepts as well as how such concepts may be preserved in a form appropriate to modern life (chapter 5), and conclude by illustrating his own attempt at such a retrieval in his late reflections on the Jewish liturgy (chapter 6). In the conclusion, I note that this interpretation offers a constructive challenge to philosophers concerned with the tradition of critical theory. On the one hand, Horkheimer articulates what would be required for the fulfillment of the Enlightenment project in terms critical theorists will recognize as their own, by offering an account of the social practices that are necessary for the self-determination of the subject. Yet his presentation contests a fundamental axiom of such theorists regarding the role intelligible concepts ought to play in seeking this goal. Horkheimer defends an account of the significance of the liturgy for practices of reasoning that is quiet foreign to such theorists. Instead of setting liturgical reasoning over against a militantly “secular” Enlightenment, he demonstrates that such reasoning is integral to its fulfillment.
Keywords: Horkheimer, Max; Frankfurt School; critical theory; affect; inquiry; instrumental reason; liturgy; apophatic theology; normativity